Nanoporous SiOx plasma polymer films as carrier for liquid‐infused surfaces. Issue 8 (22nd April 2022) - Gergs, Tobias; Monti, Chiara; Gaiser, Sandra; Amberg, Martin; Schütz, Urs; Mussenbrock, Thomas; Trieschmann, Jan; Heuberger, Manfred; Hegemann, Dirk
Abstract: Liquid‐infused surfaces are based upon the infusion of a liquid phase into a porous solid material to induce slippery and repellent character. In this context, porous SiOx plasma polymer films represent a relevant candidate for a robust nanoporous carrier layer. Intermittent low‐pressure plasma etching of O2 /hexamethyldisiloxane‐derived coatings is investigated to enhance the intrinsic porosity inherent to residual hydrocarbons in the silica matrix. Simulations of the resulting Si–O ring network structure using reactive molecular dynamics indicate formation of interconnected voids with Si–OH functionalized pore walls allowing water penetration with almost Fickian diffusive behavior. The corresponding porosity of up to 18%, well agreeing with simulations, Fourier‐transform infrared spectroscopy, and ellipsometry measurements, was found to be suitable for the liquid infusion of polyethylene glycol molecules into about 80 nm thick SiOx films providing ongoing lubricating properties, thus revealing their suitability as liquid‐infused surfaces. Abstract : Nanoporous SiOx plasma polymer films are investigated as carriers for liquid‐infused surfaces. Alternating deposition from Ar/O2 /hexamethyldisiloxane plasmas and etching conditions using Ar/O2 plasmas are used to enhance porosity by removal of residual hydrocarbons leaving Si–OH functionalized pore walls. Water is able to diffuse through the pore structure showing almost Fickian behavior. Reactive molecular dynamics simulations indicate the formation of interconnected pores of about 1 nm size. Infusion of polyethylene glycol into the porous structure enables liquid‐infused surfaces with lubricating properties.